2007
DOI: 10.1038/ng2030
|View full text |Cite
|
Sign up to set email alerts
|

A six-nucleotide insertion-deletion polymorphism in the CASP8 promoter is associated with susceptibility to multiple cancers

Abstract: Caspases are important in the life and death of immune cells and therefore influence immune surveillance of malignancies. We tested whether genetic variants in CASP8, CASP10 and CFLAR, three genes important for death receptor-induced cell killing residing in tandem order on chromosome 2q33, are associated with cancer susceptibility. Using a haplotype-tagging SNP approach, we identified a six-nucleotide deletion (-652 6N del) variant in the CASP8 promoter associated with decreased risk of lung cancer. The delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
291
4
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(321 citation statements)
references
References 41 publications
22
291
4
3
Order By: Relevance
“…By means of the mRNA target gene prediction database (http://microrna.sanger.ac.uk/), we found more than 1,000 target genes of miR-27a, including some cancer-related genes, such as aspartate-specific cysteine protease (CASP8) [55], mutL homolog 1(MLH1), vascular endothelial growth factor C (VEGFC), and BCL2-associated X protein (BAX). Scott et al found that the transcription of ZBTB10 is upregulated after miR-27a antisense transfection [56].…”
Section: Discussionmentioning
confidence: 99%
“…By means of the mRNA target gene prediction database (http://microrna.sanger.ac.uk/), we found more than 1,000 target genes of miR-27a, including some cancer-related genes, such as aspartate-specific cysteine protease (CASP8) [55], mutL homolog 1(MLH1), vascular endothelial growth factor C (VEGFC), and BCL2-associated X protein (BAX). Scott et al found that the transcription of ZBTB10 is upregulated after miR-27a antisense transfection [56].…”
Section: Discussionmentioning
confidence: 99%
“…19 The decrease in caspase-8 activity was dependent on the number of deletions present (less activity in homozygotes compared to heterozygotes). In our study, the levels of luminescence were comparable among the three CASP8 genotypes (performed by comparing the level of relative luminescence units by using a homogenous luminescent assay consisting of thermostable luciferase, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These primers have been previously described. 19 Single-round PCR amplification was performed using AmpliTaq Gold DNA polymerase (Applied Biosystems, Foster City, CA, USA). Each reaction consisted of 10x Taq buffer, 25 mM MgCl 2 , 1 μM of reverse primer, 1 μM of forward primer, 1 unit of AmpliTaq Gold, 150 μM dNTP mix and approximately 100 ng of subject DNA.…”
Section: Fragment Size Analysismentioning
confidence: 99%
See 2 more Smart Citations